Neo-racism and the Criminalization of China - Lee, Jenny (Journal of International Students, 2020)
This essay argues that neo-racism undermines the U.S.’s role as a global leader in higher education, considering the risks to public health, personal freedoms, and rights. With the rise of national protectionism, universities are and must remain international. Knowledge is fundamentally borderless, and yet higher education is being bordered by neo-racism. Neo-racist barriers to international migration, collaboration, and exchange limit higher education as well as our universities. Neo-racism limits our freedoms, it limits our rights, and now limits our ability to respond to COVID-19 effectively. Neo-racist barriers must be called out and addressed.